Strengthening The Right To Freedom Of Opinion On The Fundamental And Constitutional Rights Of Social Media Users Based On Collaboration Of The 1945 Constitution And The Uu Ite In Indonesia - Eddy, Triono; Medaline, Onny (CV. Inara, 2022)
Freedom of thought and expression is regulated in the fourth amendment to the 1945 Constitution Article 28 E paragraph (3) Everyone has the right to freedom of association, assembly, and expression. Freedom of expression, including freedom of opinion, is one of the most basic rights in the life of the state. At this time there has been a new law known as cyber law as the equivalent of cyber law, namely a law relating to the use of information technology called Cyber Law and Mayantara Law which is summarized in a statutory regulation, namely Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). The problem of this research is the extent to which the clarity of the regulation of opinion contained in the legislation and then how the legal protection is applied to social media users in terms of expressing their opinions. This research approach is a descriptive normative juridical law research. This study uses materials that are in accordance with the research conducted which is the result of library research, from library research secondary data is collected which includes primary legal materials, secondary legal materials, and tertiary legal materials. The analytical tool used is SWOT. This study aims to examine the right to freedom of expression for social media users in relation to the laws and regulations, namely the 1945 Constitution, the UU ITE, and several cases of violations of the laws and regulations that have occurred and are currently occurring in the community.